2017
DOI: 10.1080/09638288.2017.1367425
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of participating in life after spinal cord injury – advice for health professionals arising from an examination of shared narratives

Abstract: The proposed participation promotion framework is grounded in the narratives of the research group but needs to be tested before it can be endorsed for practice. Implications for Rehabilitation In order to promote participation in life after spinal cord injury rehabilitation professionals can help people with spinal cord injury to negotiate the world, build and maintain a support crew and access equipment and technology. Spinal cord injury rehabilitation professionals can encourage people with spinal cord inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(40 citation statements)
references
References 44 publications
1
36
0
3
Order By: Relevance
“…These findings are confirmed in the literature, which also points to a spirit of struggle, religious beliefs, involvement in various activities and in the labor market, voluntary and leisure activities, and asking for help (4,9,(12)(13) .…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…These findings are confirmed in the literature, which also points to a spirit of struggle, religious beliefs, involvement in various activities and in the labor market, voluntary and leisure activities, and asking for help (4,9,(12)(13) .…”
Section: Discussionsupporting
confidence: 75%
“…We found that the ultimate goal of rehabilitation is to recover and retain the highest possible level of autonomy of the individual in order to maximize their participation. The role and efficiency of rehabilitation in the autonomy of disabled individuals are highlighted, pointing out that the rehabilitation professional is concerned with maintaining the autonomy of these individuals by encouraging their participation in activities they value, ensuring that their personal, social and health needs are met, and cooperating to reduce the various limitations related to disease in social activities (6,11,13) .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations